Selection of stably expressed internal control genes in circulating polymorphoneutrophils of periparturient Sahiwal (Bos indicus) cows - MUKESH, MANISHI; KISHORE, AMIT; SHARMA, ANKITA; TANTIA, M S; KATARIA, R S; MOHANTY, A K; SODHI, MONIKA (The Indian Journal of Animal Sciences, 2018)
Around parturition, animal undergoes a state of immune-suppression and become more susceptible to pathogens. This study was aimed to identify appropriate internal control genes (ICG) for transcriptional studies in polymorphoneutrophils (PMN)of Sahiwal (Bos indicus) cows during the periparturient period. The study involved 4 periparturient Sahiwal cows (–21 days to 0 day to +21 days relative to parturition) and 10 known internal control genes (ICG)from different functional classes. ForqPCR reaction following conditions were employed: 2 min at 50°C, 10 min at 95 °C, 40 cycles of 15 s at 95 °C (denaturation) and 1 min at 60°C (annealing + extension).To measure the transcript stability of 10 ICG genes, threesoftwareprogrammes;geNorm, Normfinder and BestKeeper were used. All the genes showed acceptable expression stability as per the recommended threshold values. The geNorm analysis showed RPS9, RPS15A and RPS23 genes to be most stably expressed while HMBS and HPRT1 showed least stability.The expression stability for all the 10 ICG were within the acceptable range (M value <1.5).The pair wise variation analysis recommended the use of RPS9, RPS15Agenes for normalization. The geNorm and Normfinder identified same set of most and least stable genes. BestKeeper analysis identified ACTB, RPS9/ B2M,RPS23, RPS15A genes showing consistent expression while HMBS and HPRT1 showed relatively much higher variability. Our analysis identified RPS9, RPS15Aand ACTBgenesassuitable ICG to provide accurate normalization totranscriptional dataof PMN during the periparturient stages of Indian cows.